2021
DOI: 10.1155/2021/6694890
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Gender-Based Violence and Its Associated Factors among Female Night Students in Bahir Dar City, Amhara Region, Ethiopia

Abstract: Background. Gender-based violence (GBV) is a major public health issue that affects the health and well-being of millions of young people worldwide each year. Gender-based violence was prevalent throughout Sub-Saharan Africa. However, research in Africa is extremely diverse. Objective. The purpose of this study is to determine the extent and risk factors of gender-based violence among night female students in Bahir Dar, Ethiopia. Methods. This cross-sectional study was conducted among 788 elementary and high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Poor educational performance among high school students were associated with gender-based violence in our study those who have poor educational status has 4.5 times more at risk of having gender based violence or experienced gender-based violence than their counterparts these finding shows similarities with the study conducted at Bahirdar city high school female students according to the study those students who had poor educational performance were three times the odds of gender-based violence than those who have good school performance [ 27 ]. Another study conducted in Menkorer High school, North west Ethiopia indicated that respondents with current educational status of good and above were less likely to be a victim of gender based violence by nine Percent when compared with students who have poor educational status [ 6 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Poor educational performance among high school students were associated with gender-based violence in our study those who have poor educational status has 4.5 times more at risk of having gender based violence or experienced gender-based violence than their counterparts these finding shows similarities with the study conducted at Bahirdar city high school female students according to the study those students who had poor educational performance were three times the odds of gender-based violence than those who have good school performance [ 27 ]. Another study conducted in Menkorer High school, North west Ethiopia indicated that respondents with current educational status of good and above were less likely to be a victim of gender based violence by nine Percent when compared with students who have poor educational status [ 6 ].…”
Section: Discussionsupporting
confidence: 72%
“…Those students who do not have the free discussion about reproductive health issues had 2.7 times odds of gender-based violence than their counterparts this finding is supported by the study conducted in other areas of the country a study conducted at Bahirdar city in Amhara region reported that, lack of experience of discussion about sexual and reproductive health issues with their family and or friends has increased almost four times the odds of GBV as compared to their counterparts [ 27 ]. Another study conducted at Gondar showed that significant association between the outcome variable gender based violence and the independent variable of free discussion about reproductive health issues [ 30 ].…”
Section: Discussionmentioning
confidence: 73%
“…In Nigeria, like in most African societies, domestic violence is gendered and culturally patterned. Liyeh et al [14] cited in Obayi [3] aver that gender-based violence is a "serious, lifethreatening global problem that affects women, girls, boys, and men, and it is widely underreported in all settings". "Domestic violence is more dangerous than cancer, motor vehicle accidents, war, and malaria.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Different factors contribute to the occurrence of gender-based violence among female students, such as low academic performance, lack of sexual and reproductive health education, and poor family involvement. These factors increased significantly the risk of gender-based violence ( 15 ). Additionally, female students who were living alone in a rented house or had a partner (husband or boyfriend) also had higher probabilities of suffering gender-based violence ( 16 ).…”
Section: Introductionmentioning
confidence: 99%